Comparative Analysis of Transport and Storage Information Systems of the European Union and Serbia Using Fuzzy LMAW and MARCOS Methods - Radojko Lukic (Economy, Business and Development: An International Journal (EB&D), 2023)
Information and communication technology is one of the critical factors for the business success of modern transport and storage. Therefore, it is important to research the information system of transport and storage from different aspects. In this paper, starting from that, a comparative analysis of the selection and ranking of the information system of transport and storage in the European Union and Serbia is carried out based on the FLMAW - MARCOS method. The obtained empirical results show that the top five countries according to the information system of transport and storage include: Malta, the Netherlands, Lithuania, Spain and Slovenia. Germany ranked thirteenth, France sixteenth and Italy eighteenth. Bulgaria (in twenty-fifth place) and Romania (in twenty-sixth place) are in an unenviable position. In the last (twenty-eighth) place is Belgium. Serbia is in twenty-second place, and is in a worse position compared to the countries in the region (Slovenia - fifth place and Croatia - fifteenth place). In order to improve the information system in the future, a greater application of information and communication technology in transport and storage is necessary, especially in countries ranked at a lower level. The effects of this are to improve the overall transport and storage performance.
Keywords: D22; L81; M31; M41; P25; O32; 330; Information system; transport; and storage; European Union; Serbia; FLMAW-MARCOS method